Die begrip verganklikheid as komplekse kode in enkele werke van Hennie Aucamp - Garbers, Marius Wolhuter (Rhodes University, Faculty of Humanities, School of Languages, 1989)
Mortality has always been a popular theme in literature. By means of a semiological and narratological approach, it has been endeavoured in this study to prove that transience comprises a complex code constituted by a whole series of codes. In each of the chosen volumes one specific short story is analysed and all the codes related to transience are defined and described. Then these codes are discussed within the context of the volume as a whole. The following codes have been identified and analysed: death and death related codes, decay, distress, frustration, emptiness, loneliness observe, look and see, reproduction, the code of ageing, youth/ageing, lost love, time. The following texts of Aucamp have been used as the object of study: Die Hartseerwals, Spitsuur and 'n Bruidsbed vir Tant Nonnie. The reason these texts were selected, is twofold: They represent the early works of the author. The continuity is essential for making meaningful deductions. The final conclusions are: Man's bond with an environment which is characterised by continual change, influences his existence and makes his life a tentative experience. Transience involves more than merely ageing, obsolescence and death. Transience is a complex experience, related to the physical and mental in man. Besides ageing, sexuality contributes to man's downfall. Loneliness, isolation and frustration determine his actions and stress his experience of transience. The result is a painful experience of life.
Keywords: Aucamp, Hennie -- Criticism and interpretation